Efectivity of The Combination of Lateral and Semi fowler Positions Against Hemodynamics of Heart Failure Congestive in GrandMed Hospital Lubuk pakam - Pitriani Pitriani; Pratiwi Christa Simarmata; Samuel Ginting; Syatriawati Syatriawati; Kardina Hayati (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Congestive Heart Failure (CHF) remains a major health problem worldwide, with high prevalence and significant mortality rates. This condition is characterized by the heart’s inability to pump blood adequately to meet tissue demands, leading to hemodynamic disturbances such as impaired respiration and reduced oxygen saturation. One of the simple nursing interventions that is believed to improve these conditions is body positioning. The combination of lateral and semi-fowler positions is expected to enhance venous return, optimize lung expansion, and support ventilation in CHF patients. This study aimed to evaluate the effectiveness of combining lateral and semi-fowler positions in improving hemodynamic status, specifically respiratory pattern and oxygen saturation, among patients with congestive heart failure at GrandMed Hospital, Lubuk Pakam.A pre-experimental design with a one-group pretest-posttest approach was employed. A total of 23 respondents were selected using purposive sampling based on inclusion criteria. Respiratory rate and oxygen saturation were measured before and after the intervention. Data were analyzed using the Wilcoxon Test with a significance level of α = 0.05.Prior to the intervention, most patients experienced tachypnea (78%) and low oxygen saturation (52.2%). Following the intervention, improvements were observed, with 60.9% of patients achieving normal respiratory patterns and 56.5% showing adequate oxygen saturation, while only 8.7% remained in the low category. Statistical analysis revealed significant differences in respiratory rate (mean difference = 0.391; Z = -3.873; p = 0.001) and oxygen saturation (mean difference = 0.783; Z = -3.873; p = 0.001).The combination of lateral and semi-fowler positions proved effective in reducing tachypnea and enhancing oxygenation in patients with congestive heart failure. This intervention may serve as a simple, practical, and applicable nursing measure to support hemodynamic stability in CHF patients.